Concomitant Use of Glycoprotein IIb/IIIa Inhibitor and Streptokinase after Unsuccessful Rescue Angioplasty - Sousa,José Marconi Almeida de (2002)
A 38-year-old man with acute myocardial infarction in the lower wall affecting the right ventricle underwent thrombolytic treatment with streptokinase. Approximately 2 hours after the thrombolytic treatment started, he presented with signs of coronary reocclusion. He underwent emergency cineangiocoronariography that revealed that his right coronary artery was completely occluded by a clot. He unsuccessfully underwent angioplasty and stent implantation. After the concomitant use of glycoprotein IIb/IIIa inhibitor, coronary TIMI III flow was achieved without additional dilations, and he was discharged from the hospital 5 days later with no further complications.